2021
DOI: 10.1016/j.rse.2021.112691
|View full text |Cite
|
Sign up to set email alerts
|

Direct reflectance transformation methodology for drone-based hyperspectral imaging

Abstract: Multi-and hyperspectral cameras on drones can be valuable tools in environmental monitoring. A significant shortcoming complicating their usage in quantitative remote sensing applications is insufficient robust radiometric calibration methods. In a direct reflectance transformation method, the drone is equipped with a camera and an irradiance sensor, allowing transformation of image pixel values to reflectance factors without ground reference data. This method requires the sensors to be calibrated with higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…The recent review by Aasen et al [43] suggested various techniques for radiometric processing. The state-of-the-art techniques provide tools for atmospheric correction [44,45]. However, the methods for accounting for the reflectance anisotropy are still missing from most of the presented processing chains; one of the existing solutions is the radiometric block adjustment presented by Honkavaara et al [46].…”
Section: Discussionmentioning
confidence: 99%
“…The recent review by Aasen et al [43] suggested various techniques for radiometric processing. The state-of-the-art techniques provide tools for atmospheric correction [44,45]. However, the methods for accounting for the reflectance anisotropy are still missing from most of the presented processing chains; one of the existing solutions is the radiometric block adjustment presented by Honkavaara et al [46].…”
Section: Discussionmentioning
confidence: 99%
“…The preprocessing steps of Rikola hyperspectral image mainly include [25], [26]: 1) Format conversion and dark current correction (using Hyperspectral Imager software); 2) Bands registration (using RegMosaic software); 3) Image mosaic (using Agisoft Photoscan Professional software).…”
Section: A Uav Hyperspectral Imagesmentioning
confidence: 99%
“…A particular advantage of drone imagery over satellite/airborne imagery regarding shallow-water inversion is the fact that the first does not require atmospheric correction. The atmospheric effects on drone-based imagery are considered minor for bright targets in the visible spectrum and when images are taken from less than 150 m altitude under favorable weather conditions (Suomalainen et al, 2021). However, the use of a calibration reflectance panel is required for obtaining reflectance values adjusted for incoming radiance.…”
Section: Implications In Coastal Seafloor Monitoringmentioning
confidence: 99%